Pengaruh latihan kekuatan otot tangan, daya tahan otot dan keseimbangan terhadap ketepatan shooting game petanque di UKM Petanque Upgris - Wawan Adi Saputro Sukawi; Osa Maliki; Fajar Ari Widiyatmoko (YLPK Mahardhika, 2021)
This research is motivated by the problem in this study, namely weak hand muscle strength, muscle endurance and balance to shooting games, some UPGRIS students take part in Petanque UKM, some of them are students who have hand muscle strength, muscle endurance in throwing something is lacking and so is the balance of the body. The purpose of this study was to determine the effect of hand muscle strength, muscle endurance and balance on the accuracy of shooting games at UKM Petanque UPGRIS and to determine the causes of the lack of accuracy in the shooting game Petanque. The method used is quantitative research methods with the type of research model True-Experimental Design Pre-test Post-test Two Group design. The population and sample in this study were 10 petanque athletes at the PGRI University of Semarang. This sampling technique uses total sampling. The method of data analysis used paired sample test with a significance level of 5%. The results showed that there was an effect of hand muscle strength training, muscle endurance and balance on the accuracy of shooting game Petanque which was expressed through the results of hypothesis testing with paired sample t-test with count = -7.571 and t-table = 2.777. Then t_count> t-table so that Ho is rejected and Ha is accepted, while based on the significant value because the value is sig. = 0.002 with a confidence level of 95%, then Sig. > ? (0.05). So that Ho was rejected. This study concludes that there is an effect of hand muscle strength training, muscle endurance and balance on the accuracy of the Petanque shooting game at the UKM Petanque UPGRIS club. Suggestion, hand muscle strength training, muscle endurance and balance are used as training media so that they can help athletes improve shooting accuracy.